Assessing the Effect of Rewards on Academic Staff Performance in Uganda's Public Universities - Injikuru, Justine; Etomaru, Irene; Onen, David (East African Journal of Education Studies, 2024)
The persistent decline in academic staff performance at Uganda's public universities prompted this study to investigate the effect of rewards on their performance. Using an exploratory sequential research design, data were collected from 350 academic staff through self-administered questionnaires and analyzed using descriptive statistics and linear regression, alongside interviews with 13 academic staff, which were analyzed using content analysis. The findings reveal that while rewards are a statistically significant predictor of performance, their influence is modest, accounting for 7.6% of the variation in teaching performance, 12.5% in research performance, and 9.6% in community service performance. These results suggest that while rewards positively impact academic performance, their limited predictive power indicates that other factors play a more significant role. The qualitative findings supported the quantitative data, highlighting the importance of additional influences such as professional development, workplace environment, and institutional support. As a result, it is recommended that public universities not only strengthen reward systems but also adopt a comprehensive approach that addresses these other factors. This holistic strategy will help create a more conducive academic environment and ultimately enhance the overall performance of academic staff